2009
DOI: 10.1097/npt.0b013e3181c1fc0b
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a New Application of Noninvasive Brain Computer Interface (BCI): A Case Study of Training for Recovery of Volitional Motor Control After Stroke

Abstract: BCI + FES training for motor learning after stroke was feasible. A highly accurate brain signal control was achieved, and this signal could be reliably used to trigger the FES device for isolated index finger extension. With training, volitional control of isolated finger extension was attained in a small number of sessions. The source of motor recovery could be attributable to BCI, FES, combined BCI + FES, or whole arm or hand motor task practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
212
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(224 citation statements)
references
References 23 publications
6
212
0
2
Order By: Relevance
“…It is currently not known how signals arising from the periphery are attenuated as they are conveyed to the motor cortex. Indeed, functional electrical stimulation (FES) is another therapy that has been used specifically to target the TA muscle after stroke either alone (Burridge et al 1997;Everaert et al 2010;Knash et al 2003;Lyons et al 2002;Thompson and Stein 2004) or in combination with a BCI (Cincotti et al 2012;Daly et al 2009;Li et al 2014). FES uses a higher-frequency and -intensity stimulation to alter the excitability of the cortical projections to the target muscle than that applied in the present study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is currently not known how signals arising from the periphery are attenuated as they are conveyed to the motor cortex. Indeed, functional electrical stimulation (FES) is another therapy that has been used specifically to target the TA muscle after stroke either alone (Burridge et al 1997;Everaert et al 2010;Knash et al 2003;Lyons et al 2002;Thompson and Stein 2004) or in combination with a BCI (Cincotti et al 2012;Daly et al 2009;Li et al 2014). FES uses a higher-frequency and -intensity stimulation to alter the excitability of the cortical projections to the target muscle than that applied in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…The hypothesis is that the afferent signal generated artificially induces central nervous system plasticity because it is in causal association with the cortical activity associated with the intention to move. Several research groups have recently provided evidence that this type of BCI leads to functional improvements in upper limb or hand function (Ang et al 2010;Broetz et al 2010;Cincotti et al 2012;Daly et al 2009;Kasashima-Shindo et al 2015;Li et al 2014;Mukaino et al 2014;Pichiorri et al 2015;Ramos-Murguialday et al 2013;, although others have found no changes (Ang et al 2014;Buch et al 2008) and data are lacking for the use of such a BCI for altering lower limb function (Teo and Chew 2014). These studies report evidence for neuroplasticity, typically inferred from an improved performance of the BCI (Buch et al 2008;Li et al 2014), from alterations in the amplitude (Broetz et al 2010;Cincotti et al 2012;Li et al 2014;Pichiorri et al 2015) or latency ) of the extracted electroencephalographic (EEG) signal, or by functional magnetic resonance imaging (fMRI) .…”
mentioning
confidence: 99%
“…Likewise, preliminary evaluations in individuals with chronic stroke suggest that rehabilitation enabled by BMI-guided electrical stimulation of arm muscles may promote unexpected gains in function (Fig. 2, A and F) (86,87).…”
Section: Multisystem Neurorehabilitationmentioning
confidence: 99%
“…ОРИГИНАЛЬНЫЕ СТАТЬИ муляция, изучению электрических и нейрохимиче-ских механизмов воздействия которой посвящено на сегодняшний день большинство исследований [1][2][3][4][5][6][7][8][9][10][11]. Научных работ, посвященных изучению эффектов низкочастотной магнитной стимуляции на головной мозг, значительно меньше [9,11,12].…”
Section: ключевые слова: постинсультная реабилитация транскраниальнаunclassified